Social wasps (Polistinae) from Pampa Biome: South Brazil, Northeastern Argentina and Uruguay - Somavilla, Alexandre; Köhler, Andreas (EntomoBrasilis, 2017)
Abstract. This study aimed to determine social wasps’ species from Pampa Biome. Were examined samples of social wasps from south-central of Rio Grande do Sul state (Brazil), parts of Buenos Aires, Entre Rios, Corrientes, Cordoba, Santa Fé and La Pampa provinces (Argentina) and in Uruguay maintained in the Coleção Entomológica de Santa Cruz do Sul (Santa Cruz do Sul-Brazil), American Museum of Natural History (USA), Natural History Museum (London-United Kingdom) and Muséum National d’Histoire Naturelle (Paris-France). Thirty species were recorded: Agelaia (01), Brachygastra (01), Mischocyttarus (04), Polistes (15), Polybia (08) and Protonectarina (01). Vespas sociais do Bioma Pampa: sul do Brasil, nordeste da Argentina e Uruguai. Resumo. Este estudo objetivou determinar as espécies de vespas sociais provenientes do Bioma Pampa. Foram examinadas vespas sociais provenientes de coletas da região centro-sul do Rio Grande do Sul (Brasil), parte das províncias de Buenos Aires, Entre Rios, Corrientes, Cordoba, Santa Fé e La Pampa (Argentina) e Uruguai depositadas na Coleção Entomológica de Santa Cruz do Sul (Santa Cruz do Sul-Brasil), American Museum of Natural History (Nova Iorque-USA), Natural History Museum (Londres-Reino Unido) e Muséum National d’Histoire Naturelle (Paris-França). Trinta espécies foram registradas: Agelaia (01), Brachygastra (01), Mischocyttarus (04), Polistes (15), Polybia (08) e Protonectarina (01).